La « femme·eux·ze » musique québécoise : La recherche sur les genres, les sexualités et autres pratiques non dominantes en musique au Québec (1874-2022) - Blais-Tremblay, Vanessa (Nouveaux cahiers de recherche, 2023)
C’est là un ouvrage de référence qui présente la recherche sur la musique, les genres et les sexualités, et plus largement la vie musicale non dominante au Québec depuis le dernier quart du XIXe siècle jusqu’à aujourd’hui. Issu des travaux réalisés en 202-2022 par le pôle universitaire DIG! Différences et inégalités de genre dans la musique au Québec (D!G), un réseau interdisciplinaire et intersectoriel qui réunit les chercheur·ses, publics, artistes et autres professionnel·les de la musique qui s’intéressent à cette thématique, l’ouvrage comprend une revue de la littérature et une bibliographie de plus de 800 ressources scientifiques.

Les îles (2011) d’Isabelle Panneton et l’héritage de Philippe Boesmans : généalogie d’une démarche compositionnelle - Brasset, Marie-Pierre (Circuit : musiques contemporaines, 2021)
Dans les années 1980, après ses études auprès de Gilles Tremblay, Isabelle Panneton fait la rencontre de Philippe Boesmans lors d’un passage du compositeur belge à Montréal. Impressionnée par sa musique, elle se rendra en Belgique pour y suivre des leçons de composition avec lui de 1984 à 1987. Cette période sera déterminante pour la compositrice, ouvrant toute grande la porte à l’émergence de sa personnalité musicale. Ce texte retrace les moments forts du passage d’Isabelle Panneton chez le compositeur belge et met en lumière les liens qui les unissent, en guise de prélude à l’analyse de son trio Les îles pour violon, violoncelle et piano.
Keywords: Belgique; Belgium; Isabelle Panneton; Philippe Boesmans; chamber music; développement motivique; motivic development; musique de chambre

Chronologie de plus de cent ans de présence féminine dans la création d'œuvres musicales au Québec : un premier survol - Lefebvre, Marie-Thérèse (Les Cahiers de la Société québécoise de recherche en musique, 2021)

Avant-propos. Björk, Montréal et le Nunavut - McKinley, Maxime (Circuit : musiques contemporaines, 2021)
An article from Circuit, on Érudit.

TAGS de Joane Hétu et TanGRAM de Danielle Palardy Roger : signatures plurielles et figure continue - Dall’Ara-Majek, Ana (Circuit : musiques contemporaines, 2020)
TAGS by Joane Hétu and TanGRAM by Danielle Palardy Roger are two written works that showcase graphic scores in improvised music. TAGS creates an encounter between Ensemble SuperMusique, the saxophone quartet Quasar, and the Bozzini Quartet. The musicians make “sound graffiti” on an imaginary wall represented by a sequence of timed sections on a descriptive score where the composer uses different instrumental combinations. Using an aesthetic of articulated gestures, the work is made through these multiple signatures. TanGRAM brings together twenty instrumentalists from Ensemble SuperMusique. The game of Tangram is represented in the form of a graphic score where each piece has specific musical properties to be interpreted by the musicians. Rich in combinatorial and symmetrical games, the work presents Orion: a continuous figure, a slowly moving flow where each musician seeks their own way in a global sound.
Keywords: Analyse musicale; Danielle Palardy Roger; Joane Hétu; Musical analysis; graphic score; improvised music; musique improvisée; partition graphique

Jocelyne Binet's Cycle de Mélodies: Unearthing a Forgotten Song Cycle - Hoch, Matthew (Journal of Singing, 2020)
Montreal composer Jocelyne Binet's "Cycle de Melodies sur des Poemes de Paul Eluard" was programmed in 1955 by the French baritone Gerard Souzay in a performance that was most likely the world premiere. Unfortunately, Binet's song cycle never was published, and the work soon was forgotten. In the fall of 2016, the author discovered Bineet's original handwritten manuscript pages in holdings of Bibliotheque et Archives Nationales du Quebec and began the process of reconstructing the score. This article discusses the editorial journal undertaken when resurrecting Binet's forgotten song cycle, which was subsequently published in 2018 by Classical Vocal Reprints.
Keywords: Archives & records; Education; French language; Manuscripts; Music; Musical performances; Online data bases; Piano; Spelling; Vocal music

Ageing with Waves: The Im/material Worlds of Two Quebec Ondists - Madden, David (A Senior Moment: Cultural Mediations of Memory and Ageing, 2020)
Ageing and memory - two aspects of life everybody has to face eventually. The contributions to this volume explore the cultural mediations of these categories. Through a series of approaches focused on practices and acts of memory, narratives, reminiscence, representation and collective memory, they seek to better understand and critically reflect on how ageing is experienced in variegated ways across the lifespan. By covering a variety of phenomena, from biopics, music by the elderly, and artefacts, among other, they all contribute to further the understanding of memory as a cultural process always in the making - situated in particular contexts, and shaped by its material conditions of existence.

Tuning a Room: Designs for Hearing According to Nancy Tobin - Rewa, Natalie (Canadian Theatre Review, 2020)
In this review, I discuss the architectonics of sound composition according to sound artist and designer Nancy Tobin. This chapbook advocates for a comprehensively integrated presence of a sound artist in the processes of rehearsal and espouses a dramaturgy of hearing. Tobin’s distinction between hearing and listening gives forth onto a series of self-studies of her experience of spatial and temporal arrangements presented in the form of e-mails to mentees. Her appreciation for the acoustics of the performance space extends to the composition of sound to be heard (on occasion as boldly interventionist) and the technologies of broadcasting it: the choice and placement of speakers, as well as their interaction with the performers. Tobin argues for a definition of sound composition for performance as a complex collaboration with the production—curatorial in terms of the space of ephemerality. My review concurs with the efficacy of her approach by my recognition of the moments in productions that have remained as some of the most memorable of my theatregoing.
Keywords: Nancy Tobin; acoustic space; rehearsal processes; sonic/acoustic dramaturgy; sound artist; speaker specifications and broadcasting sound